Experimental analysis of real-world emissions using ultra-low carbon intensity biodiesel for a light-duty diesel vehicle in Monterrey metropolitan area. (1st June 2022) - Martínez-Martínez, Simón; Rosa-Urbalejo, Daniel de la; Rua-Mojica, Luis F.; Hernández-Altamirano, Raúl; Mena-Cervantes, Violeta Y.
Abstract: Experiments were conducted employing a light-duty diesel vehicle filled with complete characterized 5%, 10%, and 20% volume ultra-low carbon intensity waste cooking oil biodiesel blends for determining real-world emission rates and emission factors, which were compared to those of petroleum diesel for three driving modes, namely, low, medium, and high cruise speed, and transient conditions. Chemical characterization of blended and pure fuels allowed to discard any quality influences on the fuel performance during the on-road tests. Five percent volume blends showed the best all-around performance of all blends in comparison with petroleum diesel in terms of emissions reduction, along with its lowest fuel consumption, hence, representing a potential blend that can be considered as good additive for petroleum diesel, applicable only at the specific conditions of the present work. The benefit from the use of ultra-low carbon intensity biodiesel blends was clear from greenhouse gases emissions point of view, given the lifecycle emission diminishing of 93.8% mass in CO2 equivalent emissions, if the biodiesel is produced using waste cooking oil collected within the city limits. Highlights: A local driving cycle for the city of Monterrey, Mexico is appraised. Real-world driving modes at cruise speed and transient conditions were performed. Lifecycle emission diminishing 93% in CO2 equivalent emissions using waste cocking oil. All the biodiesel blends emissions were below the current Euro 6 standard. Any quality influences on the fuel performance during on-road test were discarded.